To layer or not to layer: architectural considerations on autonomic communications. (5th December 2006) - Gu, Xiaoyuan; Wolf, Lars
We introduce a new communication paradigm dubbed Autonomic Communications, for which context-awareness and distributed policy-based management plays a key role. An extensive study of network architectures is performed, followed by our vision on network architecture for Autonomic Communications, with the POEM model and its protocol design.